Food insecurity increases the risk of malnutrition among community-dwelling older adults. (January 2019) - Grammatikopoulou, Maria G.; Gkiouras, Konstantinos; Theodoridis, Xenophon; Tsisimiri, Maria; Markaki, Anastasia G.; Chourdakis, Michael; Goulis, Dimitrios G.
Highlights: The majority of older adults were either malnourished or at risk of malnutrition, and experienced a great prevalence of food insecurity. Food insecurity markedly increased the risk for malnutrition. Food insecurity was associated with lower education, reduced monthly income and low diet quality. Malnutrition risk was associated with old age, smoking, low BMI and waist perimeter, single partnership status and reduced appetite. Abstract: Objectives: To assess the prevalence of malnutrition and food insecurity (uncertainty, or limited ability to acquire acceptable foods through socially acceptable ways), among non-hospitalised, non-institutionalised, community-dwelling older adults, and to identify possible dietary, socioeconomic and health factors associated with them. Study design: Cross-sectional, with 207 older adult participants inhabitants of Thessaloniki and Kavala, Greece. A medical diagnosis was not a criterion for exclusion from participation. Main outcome measures: Malnutrition risk (combined categories of "at risk of malnutrition" and "malnourished" by the Mini-Nutritional Assessment tool) and food insecurity (assessed by the Household Food Insecurity Access Scale). Results: Participants had a mean age of 72.4 ± 8.5 years; 43.5% were male and 56.5% female. The prevalence of malnutrition was 5.3%, and 48.3% were "at risk of malnutrition". The group of participants assessed as being at risk of malnutrition were significantly older, smoked, had a lower body mass index and a smaller waist circumference, reported single partnership status, and exhibited reduced appetite. Some degree of food insecurity was apparent in 69% of the participants. Food insecurity was associated with lack of higher education, reduced monthly income and low adherence to the Mediterranean diet. Additionally, food insecurity as compared with food security increased the risk of malnutrition (OR 2.63, 95% CI 1.21–5.75; p = 0.015) in the multivariate analysis. Conclusions: Given the financial difficulties experienced by the Greek older adult population over the last decade, a large proportion of them are at risk of malnutrition and experience some degree of food insecurity. With the two conditions being interrelated, early identification and management of both malnutrition and food insecurity are essential for public health and healthy ageing.